Evaluation of Clinical Findings and Treatment Results of Coronavirus Disease 2019 (COVID-19) in Pediatric Cancer Patients: A Single Center Experience - Tolunay, Orkun; Çelik, Ümit; Arslan, Ilknur; Tutun, Bugra; Özkaya, Merve (Frontiers in Pediatrics, 2022)
Objective The objective of the study is to evaluate the clinical findings and treatment results of COVID-19 in pediatric cancer patients. Study design The study was designed as a single-center retrospective observational study. Pediatric cancer patients with COVID-19 admitted to the University of Health Sciences Adana City Training and Research Hospital pediatric COVID wards from October 2020 to October 2021 were included. Clinical data and demographic characteristics were retrieved from patient files. Results A total of 45 pediatric cancer patients diagnosed with COVID-19 were included in the study. The mean age of the patients was 8.68 ± 5.16 years (range 1.5–17.5), 62.2% were men, 37.8% were Turkish citizens, and 62.2% were Syrian refugees. A total of 41 patients (91.1%) had leukemia/lymphoma, while 4 (8.9%) had solid tumors. The most common symptoms were fever (66.7%), respiratory (35.6%), and gastrointestinal symptoms (17.8%). Disease severity was evaluated as mild in 46.7%, moderate in 44.4%, and severe in 8.9% of patients. Patients presented with lymphopenia (88.9%), thrombocytopenia (73.3%), anemia (71.1%), and neutropenia (62.2%). Mean hospital length of stay was 15.18 ± 10.34 (range 6–62) days overall and 9.5 ± 2.39 (range 2 to 28) days in the PICU. Intensive care unit admission rate was 8.9%, and mortality rate was 4.4%. Median viral shedding period was 21 days (range 7–52). Conclusions Our study reveals that the mortality rate, length of hospital stay, and the need for intensive care of pediatric cancer patients with COVID-19 are higher than those of healthy children. Prospective studies with larger sample sizes are needed to further evaluate the clinical findings and treatment results of COVID-19 in pediatric cancer patients.